Quick-curing two-component hot-pressing adhesive as well as preparation method and application thereof

By adjusting the filler particle size and using specific catalysts and curing agents, a fast curing two-component hot-pressing adhesive was prepared, which solved the problem of excessive curing time of traditional adhesives, and achieved the effect of rapid curing and high tensile shear strength.

CN119505783APending Publication Date: 2025-02-25SHANGHAI JINQIANG ADHESIVE

Patent Information

Application Number
CN202411841662.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Traditional two-component polyurethane adhesives have been cured for too long in the construction and building materials industry and cannot meet customers' demand for production efficiency. Especially after the bonding surface is glued, it is necessary to continuously pressurize for 6-8 hours before the pressure is removed to obtain the finished plate.

Method used

By adjusting the particle size and type of filler, combining triethylenediamine-capped thermally sensitive catalyst and polymerized MDI as curing agents, a fast curing two-component hot-pressed glue was prepared. Component A of the adhesive includes castor oil polyol, fillers, catalysts and additives, and component B is an isocyanate curing agent.

Benefits of technology

The rapid curing of two-component hot-pressed glue is achieved, and the curing time is controlled within 3-5 minutes. At the same time, the tensile shear strength after bonding is maintained, and the storage stability of the glue is improved, meeting the lamination strength requirements between building materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of polyurethane adhesives, in particular to a quick-curing two-component hot-pressing adhesive as well as a preparation method and application thereof. Comprising a component A and a component B. The component A comprises, by weight, 20 to 60 parts of castor oil polyol, 40 to 80 parts of a filling material, 0.001 to 0.01 part of a catalyst and 0.001 to 0.006 part of an auxiliary agent, and the catalyst comprises a triethylene diamine-terminated heat-sensitive catalyst; and the component B comprises an isocyanate curing agent. The filler comprises heavy calcium carbonate and calcium oxide, and the weight ratio of the heavy calcium carbonate to the calcium oxide is (25-40): 1, so that not only can the cost be effectively reduced, but also the tensile-shear strength of the hot-pressing adhesive can be improved; and when the particle size of the filler is adjusted to be 500-2000 meshes, the tensile-shear strength after cementing can be effectively maintained within a relatively low curing time (3-5 minutes), and meanwhile, the storage stability of the sizing material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polyurethane adhesives, and more specifically to a fast-curing two-component hot-pressing adhesive and a preparation method and application thereof. Background Art

[0002] Traditional two-component polyurethane adhesives are used in the construction and building materials industry. After applying the adhesive to the bonding surface, it needs to be continuously pressurized for 6-8 hours before the pressure can be released to obtain the finished board. With the increase in market demand, this method can no longer meet customers' demand for production efficiency, and hot-pressed adhesives that can achieve rapid curing are urgently needed.

[0003] CN 110746925 B discloses a two-component fast-curing polyurethane adhesive for air filters and a preparation method thereof. The two-component fast-curing polyurethane adhesive for air filters ensures a faster curing speed by selecting polyether polyols with different molecular weights, but the curing time of the invention still requires more than 30 minutes.

[0004] CN 111704885 B A fast-curing two-component polyurethane structural adhesive and its preparation method and application. Component A of the two-component polyurethane structural adhesive is prepared from castor oil, autocatalytic polyol, tackifying resin, coupling agent, catalyst, filler, molecular sieve and silicon dioxide, and component B is prepared from toughening polyol, plasticizer, isocyanate, glass microbeads, filler, molecular sieve and silicon dioxide. The two-component polyurethane structure not only has sufficient operating time, but also can be cured quickly, but the curing time of the invention still needs more than 10 minutes. Summary of the invention

[0005] The first aspect of the present invention provides a fast-curing two-component hot-pressed adhesive, comprising a component A and a component B, wherein the component A comprises, by weight: 20-60 parts of castor oil polyol, 40-80 parts of filler, 0.001-0.01 parts of catalyst, and 0.001-0.006 parts of auxiliary agent, wherein the catalyst comprises a triethylenediamine-terminated thermosensitive catalyst; and the component B is an isocyanate curing agent.

[0006] Preferably, the castor oil polyol is purchased from Ambuja Group, model: refined grade.

[0007] Preferably, the component A comprises, by weight: 30-55 parts of castor oil polyol, 55-70 parts of filler, 0.003-0.008 parts of catalyst, and 0.001-0.006 parts of auxiliary agent.

[0008] The filler includes at least one of heavy calcium carbonate, light calcium carbonate, montmorillonite, calcium oxide, kaolin, talc and silicon dioxide.

[0009] Preferably, the particle size of the filler is 500-2000 mesh.

[0010] More preferably, the particle size of the filler is 1000-2000 mesh.

[0011] Preferably, the filler comprises heavy calcium carbonate and calcium oxide, and the weight ratio of the heavy calcium carbonate to calcium oxide is (25-40):1.

[0012] In actual production and use, fillers are added to the adhesive. The addition of fillers can reduce the cost of the adhesive. The applicant has found that the filler includes heavy calcium carbonate and calcium oxide, and the weight ratio of the heavy calcium carbonate and calcium oxide is (25-40): 1, which can not only effectively reduce the cost, but also improve the tensile shear strength of the hot pressing adhesive. It may be that the addition of calcium carbonate reduces the force between the molecular chains, which reduces the Tg of the system. At the same time, calcium carbonate will destroy the phase separation degree of the polymer, thereby reducing the crystallinity of the soft segment in TPU. At the same time, calcium oxide can effectively absorb trace water vapor in the system and lock it inside the pores. The combined effect effectively prevents the generation and diffusion of micropores inside the polyurethane, thereby improving the tensile shear strength of the hot pressing adhesive.

[0013] Compared with the traditional hot-pressed adhesive formula, the present application greatly reduces the curing time. At the same time, since the curing time is greatly shortened, the uniformity between the adhesive layers after curing is inevitably affected. The present applicant further discovered that when the particle size of the filler is adjusted to 500-2000 mesh, the shear strength after bonding can be effectively maintained at a lower curing time (3-5min), while improving the storage stability of the adhesive. It is speculated that the particles of a specific size cause the remaining polyurethane segments to produce microphase separation, ensuring the overall fluidity of the system while avoiding aggregation between the polyurethane segments. The specific size of the soft segment and the hard segment region is maintained by the planar size of the particles, so that the uniformity of the polymerization within and between layers is effectively controlled during the curing process, reducing the phenomenon of uneven stress between systems.

[0014] Further preferably, the filler comprises heavy calcium carbonate and calcium oxide, and the weight ratio of the heavy calcium carbonate to calcium oxide is (25-32):1.

[0015] The catalyst comprises a dioctyltin catalyst, and the tin content is 10-25%.

[0016] Preferably, the catalyst is purchased from Evonik Chemicals, model: KOSMOS16.

[0017] The catalyst includes a triethylenediamine-terminated thermosensitive catalyst, which can significantly reduce the curing time and control the curing time to 3-10 minutes, and has excellent stability. The synthesis reaction of the polyurethane material is completed by the gradual transfer of hydrogen protons. The tertiary amine catalyst is easy to activate the hydroxyl compound to form ammonium cations due to the large electron cloud density on its nitrogen atom. At the same time, the nitrogen atom of the amine compound is complexed with isocyanate to reduce the reaction activation energy of isocyanate, thereby having high catalytic activity for polyurethane polymerization.

[0018] Preferably, the particle size of the heavy calcium carbonate is 1250 mesh, and the particle size of the calcium oxide is 1000 mesh.

[0019] The auxiliary agents include defoamers and leveling agents.

[0020] Preferably, the defoamer comprises an organosilicon defoamer, and further preferably, the organosilicon defoamer is purchased from BYK Chemical, model: BYK-1760.

[0021] Preferably, the leveling agent includes dimethyl silicone oil purchased from Maihao Chemical.

[0022] The applicant has found that the use of polymeric MDI with an average functionality of 2.5-3 as a curing agent in this system can further improve the shear strength to more than 10MPa within a relatively low curing time to meet the lamination strength requirements between building materials. It may be that the isocyanate groups in the isocyanate are affected by steric hindrance, resulting in differences in the activity of the isocyanate groups, and the reaction rate changes during the curing process. When there is steric hindrance around the isocyanate group, it will become more difficult for the nucleophilic reagent containing active hydrogen to approach the carbon atom of the isocyanate group, thereby reducing the reactivity of the isocyanate group. In this application, the reaction rate gradient of the polymeric MDI with a functionality of 2.5-3 decreases within the curing time to match the curing time. With the further increase in functionality, the rate difference during the reaction process is too small, and it is easy to cause a certain phase separation between the hard segment and the soft segment during the high-speed curing process, affecting the shear strength of the hot press adhesive.

[0023] Preferably, the isocyanate curing agent comprises polymeric MDI, and the average functionality of the polymeric MDI is 2.5-3.

[0024] Preferably, the viscosity (25° C.) of the isocyanate is 100-300 mPa·s, and the isocyanate content is 28-35 wt %.

[0025] Further preferably, the viscosity (25° C.) of the isocyanate is 150-250 mPa·s, the isocyanate content is 30.5-32 wt %, and the average functionality is 2.6-2.7. It is purchased from Wanhua Chemical, model: PM-200.

[0026] A second aspect of the present invention provides a method for preparing a fast-curing two-component hot-press adhesive, comprising the following steps:

[0027] S1, pouring castor oil polyol into a reaction kettle connected to a cooling system, stirring for 10-30 minutes, adding filler and stirring to mix evenly to obtain a mixture;

[0028] S2, adding the catalyst and the auxiliary agent into the mixture, stirring evenly, to obtain component A;

[0029] S3, take another isocyanate curing agent and use it as component B.

[0030] A third aspect of the present invention provides an application of a fast-curing two-component hot-pressed adhesive for bonding building panels.

[0031] The building board material comprises at least one of rock wool, glass magnesium board, honeycomb board, gypsum, aluminum honeycomb, magnesium oxysulfide, silica rock, color steel board, color-coated aluminum alloy board, stainless steel board and titanium zinc board.

[0032] The second aspect of the present invention provides a preparation method comprising the following steps:

[0033] Beneficial effects:

[0034] 1. The filler includes heavy calcium carbonate and calcium oxide, and the weight ratio of the heavy calcium carbonate to calcium oxide is (25-40):1, which can not only effectively reduce the cost, but also improve the tensile shear strength of the hot pressing adhesive.

[0035] 2. When the particle size of the filler is adjusted to 500-2000 mesh, the tensile shear strength after bonding can be effectively maintained at a relatively low curing time (3-5 min), while the storage stability of the adhesive can be improved.

[0036] 3. In this system, polymerized MDI with an average functionality of 2.5-3 is used as a curing agent, and castor oil polyol is used to further increase the shear strength to more than 10 MPa within a relatively short curing time, so as to meet the lamination strength requirements between building materials.

[0037] 4. The catalyst includes a triethylenediamine-terminated thermosensitive catalyst, which can significantly reduce the curing time and control the curing time to 3-5 minutes, while having excellent stability.

[0038] 5. The catalyst includes a dioctyltin catalyst with a tin content of 10-25%, which can meet the lamination of 3-7 layers of building boards and has an excellent material breaking effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1This is the material breaking effect after the tensile shear test of Example 1.

[0040] Figure 2 This is the material breaking effect after the tensile shear test of Example 2.

[0041] Figure 3 This is the material breaking effect after the tensile shear test of Example 3. DETAILED DESCRIPTION

[0042] Example 1

[0043] A fast-curing two-component hot-pressing adhesive consists of a component A and a component B. The component A, measured by weight, specifically comprises: 40 parts of castor oil polyol, 60 parts of filler, 0.0035 parts of catalyst, and 0.002 parts of auxiliary agent, wherein the catalyst is a triethylenediamine-terminated thermosensitive catalyst; and the component B is an isocyanate curing agent.

[0044] The catalyst was purchased from Evonik Chemicals, model: KOSMOS16.

[0045] The filler includes heavy calcium carbonate (Hunan Haocheng Technology Co., Ltd.) and calcium oxide (Jiangxi Aote Technology Co., Ltd.), and the weight ratio of the heavy calcium carbonate to calcium oxide is 58:2.

[0046] The auxiliary agent is an organosilicon defoamer and a leveling agent, and the weight ratio of the organosilicon defoamer to the leveling agent is 1:1.

[0047] A method for preparing a fast-curing two-component hot-pressing adhesive comprises the following steps:

[0048] Castor oil polyol (CastorAmbuja, refined grade) was poured into a reactor connected to a cooling system (temperature controlled at 30°C), stirred for 20 minutes, 1250-mesh heavy calcium carbonate and 1000-mesh calcium oxide powder were added and stirred for 1 hour to fully mix the castor oil polyol and heavy calcium carbonate, and then a catalyst (Evonik Specialty Chemicals Co., Ltd., KOSMOS16), a silicone defoamer (BYK-1760), and a leveling agent (McHolly Chemical, dimethyl silicone oil) were added and stirred for 30 minutes before discharging the material. Component A was prepared and sealed for storage; component B was polymerized MDI (Wanhua Chemical, PM200).

[0049] The invention discloses an application of a fast-curing two-component hot-pressing adhesive, which is applied to the bonding of building panels, wherein the building panels are rock wool.

[0050] Example 2

[0051] A fast-curing two-component hot-pressing adhesive consists of a component A and a component B. The component A, measured by weight, specifically comprises: 45 parts of castor oil polyol, 55 parts of filler, 0.0030 parts of catalyst, and 0.0025 parts of auxiliary agent, wherein the catalyst is a triethylenediamine-terminated thermosensitive catalyst; and the component B is an isocyanate curing agent.

[0052] The catalyst was purchased from Evonik Chemicals, model: KOSMOS16.

[0053] The filler includes heavy calcium carbonate and calcium oxide, and the weight ratio of the heavy calcium carbonate to calcium oxide is 50:2.

[0054] The auxiliary agent is an organosilicon defoamer and a leveling agent, and the weight ratio of the organosilicon defoamer to the leveling agent is 1:1.

[0055] A method for preparing a fast-curing two-component hot-pressing adhesive comprises the following steps:

[0056] Castor oil polyol (CastorAmbuja, refined grade) was poured into a reactor connected to a cooling system (temperature controlled at 30°C), stirred for 20 minutes, 1250-mesh heavy calcium carbonate and 1000-mesh calcium oxide powder were added and stirred for 1 hour to fully mix the castor oil polyol and heavy calcium carbonate, and then a catalyst (Evonik Specialty Chemicals Co., Ltd., KOSMOS16), a silicone defoamer (BYK-1760), and a leveling agent (McHolly Chemical, dimethyl silicone oil) were added and stirred for 30 minutes before discharging the material. Component A was prepared and sealed for storage; component B was polymerized MDI (Wanhua Chemical, PM200).

[0057] The invention discloses an application of a fast-curing two-component hot-pressing adhesive, which is applied to the bonding of building boards, wherein the building boards are glass magnesium boards.

[0058] Example 3

[0059] A fast-curing two-component hot-pressing adhesive consists of a component A and a component B. The component A, measured by weight, specifically comprises: 38 parts of castor oil polyol, 62 parts of filler, 0.0028 parts of catalyst, and 0.002 parts of auxiliary agent, wherein the catalyst is a triethylenediamine-terminated thermosensitive catalyst; and the component B is an isocyanate curing agent.

[0060] The catalyst was purchased from Evonik Chemicals, model: KOSMOS16.

[0061] The filler includes heavy calcium carbonate and calcium oxide, and the weight ratio of the heavy calcium carbonate to calcium oxide is 60:2.

[0062] The auxiliary agent is an organosilicon defoamer and a leveling agent, and the weight ratio of the organosilicon defoamer to the leveling agent is 1:1.

[0063] A method for preparing a fast-curing two-component hot-pressing adhesive comprises the following steps:

[0064] Castor oil polyol (CastorAmbuja, refined grade) was poured into a reactor connected to a cooling system (temperature controlled at 30°C), stirred for 20 minutes, 1250-mesh heavy calcium carbonate and 1000-mesh calcium oxide powder were added and stirred for 1 hour to fully mix the castor oil polyol and heavy calcium carbonate, and then a catalyst (Evonik Specialty Chemicals Co., Ltd., KOSMOS16), a silicone defoamer (BYK-1760), and a leveling agent (McHolly Chemical, dimethyl silicone oil) were added and stirred for 30 minutes before discharging the material. Component A was prepared and sealed for storage; component B was polymerized MDI (Wanhua Chemical, PM200).

[0065] An application of a fast-curing two-component hot-pressing adhesive is applied to the bonding of building panels, wherein the building panels are honeycomb panels.

[0066] Comparative Example 1

[0067] Conventional cold-pressed adhesive, purchased from Shark (Shanghai) Technology Co., Ltd., model: SY8430.

[0068] Comparative Example 2

[0069] The specific implementation is the same as that of Example 1; the difference is that the catalyst in Comparative Example 2 is triethylenediamine.

[0070] Comparative Example 3

[0071] The specific implementation is the same as that of Example 1; the difference is that the catalyst in Comparative Example 3 is dibutyltin dilaurate.

[0072] Comparative Example 4

[0073] The specific implementation is the same as Example 1; the difference is that in Comparative Example 4: the weight ratio of heavy calcium carbonate to calcium oxide is 50:10.

[0074] Comparative Example 5

[0075] The specific implementation is the same as Example 1; the difference is that in Comparative Example 5: the heavy calcium carbonate is 400 mesh.

[0076] Performance Testing Methods

[0077] The performance tests were carried out in the embodiments and comparative examples, and the test data are listed in Table 1.

[0078] 1. Curing time: Mix component A and component B in a weight ratio of 100:25, and detect the specific curing time on the film surface at the test temperature.

[0079] 2. Shear strength: The bonding material is aluminum plate, the amount of glue applied is 200g / m 2 , bonding area: 312.5mm2, curing time: 24h, test method is in accordance with GB / T 7124 method. Figure 1-3 As shown, the core material destruction rate of the bonded materials reaches 100%.

[0080] 3. Storage stability: Place component A in a container and let it stand for 30 days to observe whether the colloid has stratification or precipitation.

[0081] Performance test data

[0082] Table 1

[0083] Tensile shear strength (MPa) Storage stability Curing time Example 1 10.7 good 3min Example 2 10.6 good 3.5min Example 3 10.7 good 4min Comparative Example 1 6.0 good 7h Comparative Example 2 7.0 good 35min Comparative Example 3 7.5 good 50min Comparative Example 4 8.7 good 3min Comparative Example 5 8.5 Layering 3min

Claims

1. A fast curing two-component hot pressing adhesive, characterized in that: The invention comprises component A and component B, wherein the component A comprises, by weight, 20-60 parts of castor oil polyol, 40-80 parts of filler, 0.001-0.01 parts of catalyst, and 0.001-0.006 parts of auxiliary agent, wherein the catalyst comprises a triethylenediamine-terminated thermosensitive catalyst; the component B comprises an isocyanate curing agent; and the curing time of the hot pressing adhesive is controlled to be 3-5 minutes.

2. The fast curing two-component hot pressing adhesive according to claim 1, characterized in that: The filler includes at least one of heavy calcium carbonate, light calcium carbonate, montmorillonite, calcium oxide, kaolin, talc and silicon dioxide.

3. The fast curing two-component hot pressing adhesive according to claim 2, characterized in that: The particle size of the filler is 500-2000 mesh.

4. The fast curing two-component hot pressing adhesive according to claim 3, characterized in that: The filler includes heavy calcium carbonate and calcium oxide, and the weight ratio of the heavy calcium carbonate to calcium oxide is (25-40):

1.

5. A fast curing two-component hot pressing adhesive according to claim 1 or 4, characterized in that: The catalyst includes a dioctyltin catalyst.

6. The fast curing two-component hot pressing adhesive according to claim 5, characterized in that: The auxiliary agents include defoamers and leveling agents.

7. The fast curing two-component hot pressing adhesive according to claim 6, characterized in that: The isocyanate curing agent comprises polymeric MDI, and the average functionality of the polymeric MDI is 2.5-3.

8. A method for preparing the fast-curing two-component hot-press adhesive according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1, pouring castor oil polyol into a reaction kettle connected to a cooling system, stirring for 10-30 minutes, adding filler and stirring to mix evenly to obtain a mixture; S2, adding the catalyst and the auxiliary agent into the mixture, stirring evenly, to obtain component A; S3, take another isocyanate curing agent and use it as component B for standby use.

9. An application of the fast curing two-component hot pressing adhesive according to claim 1, characterized in that: Used for bonding building panels.

10. The use of a fast curing two-component hot pressing adhesive according to claim 9, characterized in that: The building board material comprises at least one of rock wool, glass magnesium board, honeycomb board, gypsum, aluminum honeycomb, magnesium oxysulfide, silica rock, color steel board, color-coated aluminum alloy board, stainless steel board and titanium zinc board.

Citation Information

Patent Citations

  • A two-component fast-curing polyurethane adhesive for air filters and its preparation method

    CN110746925B

  • Fast-curing two-component polyurethane structural adhesive, its preparation method and application

    CN111704885B

Cited By

  • Winter jelly-resistant gel for bonding aluminum cellular board and preparation method thereof

    CN120365883A

  • Hot-pressing adhesive for ship plate and preparation method of hot-pressing adhesive

    CN121182433A

  • Hot-pressing adhesive for new aluminum material and preparation method of hot-pressing adhesive

    CN121319854A

  • Hot-pressing adhesive for full-automatic craft fireproof door and preparation method of hot-pressing adhesive

    CN121652752A